2016
DOI: 10.1371/journal.pone.0157957
|View full text |Cite
|
Sign up to set email alerts
|

Time Savings with Rituximab Subcutaneous Injection versus Rituximab Intravenous Infusion: A Time and Motion Study in Eight Countries

Abstract: BackgroundRituximab is a standard treatment for non-Hodgkin lymphoma. The SABRINA trial (NCT01200758) showed that a subcutaneous (SC) rituximab formulation did not compromise efficacy or safety compared with intravenous (IV) infusion. We aimed to quantify active healthcare professional (HCP) time and patient chair time for rituximab SC and IV, including potential time savings.MethodsThis non-interventional time and motion study was run in eight countries and 30 day oncology units. Rituximab SC data were collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
102
0
19

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(128 citation statements)
references
References 16 publications
(20 reference statements)
3
102
0
19
Order By: Relevance
“…Indeed, recent studies have reported that subcutaneous rituximab entails considerable reductions in administration, chair/bed use, active healthcare professional and overall hospital times (De Cock et al , ; Lugtenburg et al , ), without affecting the patients’ perception of their treatment and the time they had to talk to healthcare providers (Lugtenburg et al , ). Data from subcutaneous rituximab administration showed it to be a preferable treatment formulation for patients (Rummel et al , ), with improved treatment convenience, satisfaction and effect on daily living (De Cock et al , ; Rummel et al , ). Based on the accumulated clinical data, subcutaneous rituximab was approved and is currently available for the treatment of patients with DLBCL and FL (http://www.ema.europa.eu/ema/index.jsp?curl=pages/medicines/human/medicines/000165/human_med_000897.jsp&mxml:id=WC0b01ac058001d124; https://www.accessdata.fda.gov/scripts/cder/daf/index.cfm?event=overview.process&ApplNo=761064).…”
mentioning
confidence: 99%
“…Indeed, recent studies have reported that subcutaneous rituximab entails considerable reductions in administration, chair/bed use, active healthcare professional and overall hospital times (De Cock et al , ; Lugtenburg et al , ), without affecting the patients’ perception of their treatment and the time they had to talk to healthcare providers (Lugtenburg et al , ). Data from subcutaneous rituximab administration showed it to be a preferable treatment formulation for patients (Rummel et al , ), with improved treatment convenience, satisfaction and effect on daily living (De Cock et al , ; Rummel et al , ). Based on the accumulated clinical data, subcutaneous rituximab was approved and is currently available for the treatment of patients with DLBCL and FL (http://www.ema.europa.eu/ema/index.jsp?curl=pages/medicines/human/medicines/000165/human_med_000897.jsp&mxml:id=WC0b01ac058001d124; https://www.accessdata.fda.gov/scripts/cder/daf/index.cfm?event=overview.process&ApplNo=761064).…”
mentioning
confidence: 99%
“…To date, studies have shown that the safety profiles of the sc and IV formulations of rituximab are similar (Table i) 6,[9][10][11]13,14,16,17 ; however, studies have reported greater rates of gastrointestinal toxicities with the IV formulation (55% vs. 31%) 14 and of local administration-related reactions (arrs) with the sc formulation 6,9-11,13,14,17 . Of patients given the sc formulation, arrs were reported by 31%-50%; of those given the IV formulation, 4% -32% reported such reactions.…”
Section: Safetymentioning
confidence: 99%
“…A second ongoing trial, mabcute, is examining induction with sc rituximab (IV cycle 1; sc cycles 2-8) plus chemotherapy, followed by maintenance with sc rituximab at standard doses in patients with relapsed or refractory indolent nhl 9 . Upon completion of standard maintenance, responding patients will be randomized to receive additional maintenance or observation 9,10 . Preliminary data from the mabcute study presented at the American Society of Hematology meeting in 2013 showed a reduction in chair time of 64%-91% and a savings in physician time of 6.8-38.4 minutes, resulting in an expected annual chair time savings of 105.1-233.4 eight-hour days.…”
Section: Patient Preference and Time Savingsmentioning
confidence: 99%
“…Further, the potential benefits of the reduction in administration time are appreciable. It simplifies the treatment experience for both patients and health‐care professionals, reduces the burden on health‐care resources and is likely to improve patient quality of life and treatment adherence . One multinational study demonstrated reductions of between 64% and 91% in patient chair time following a switch from IV to SC administration of rituximab, which translated to a reduction of 17–33 h of chair time per patient over the first year of treatment.…”
Section: Clinical Practice Considerationsmentioning
confidence: 99%
“…Furthermore, health‐care professional time was substantially reduced, by between 7 and 38 min per session, equating to 0.9–5.1 h less resource input per patient over the first year of treatment. Patient throughput, waiting list times and hospital efficiency were greatly improved …”
Section: Clinical Practice Considerationsmentioning
confidence: 99%